2008
DOI: 10.1002/chem.200801092
|View full text |Cite
|
Sign up to set email alerts
|

Structure Elucidation and Theoretical Investigation of Key Steps in the Biogenetic Pathway of Schisanartane Nortriterpenoids by Using DFT Methods

Abstract: Rubrifloradilactone C (4), a novel bioactive nortriterpenoid, along with four other nortriterpenoids (1-3, 5) were isolated from Schisandra rubriflora. The structure of 4 was determined by extensive NMR spectral analysis, computational evidence by using the GIAO method at the B3LYP/6-311++G(2d,p)//B3LYP/6-31G(d) levels, and X-ray analysis. DFT at the B3LYP/6-311+G(d,p) level was selected to clarify the key mechanistic steps in the formation of 1 and 4 through transition-state (TS) investigations. The effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 69 publications
0
17
0
1
Order By: Relevance
“…In addition, the structure of kadpolysperin H (34) 8 and several stereogenic centers of schinortriterpenoids were mistaken by them. For example, schisandilactones B-D (239-241) 9 and lancifodilactone R (251), 10 analogues of rubrioradilactone C (220) whose structure was conrmed by X-ray diffraction, 11 should present with a 15a-OH, instead of a 15b-OH as they described. 7 Additionally, some confusing nomenclatures are found in the original articles.…”
Section: Introductionmentioning
confidence: 93%
“…In addition, the structure of kadpolysperin H (34) 8 and several stereogenic centers of schinortriterpenoids were mistaken by them. For example, schisandilactones B-D (239-241) 9 and lancifodilactone R (251), 10 analogues of rubrioradilactone C (220) whose structure was conrmed by X-ray diffraction, 11 should present with a 15a-OH, instead of a 15b-OH as they described. 7 Additionally, some confusing nomenclatures are found in the original articles.…”
Section: Introductionmentioning
confidence: 93%
“…Comparison of the 1D-NMR data of 3 with those of 1 showed that the difference was that the oxygenated quaternary C(25) of 1 was replaced by a CH group (Fig. 1) showed that 4 possessed the same planar structure as rubrifloradilactone C [11]. The significant chemical-shift differences observed in the NMR spectra between 4 and rubrifloradilactone C were associated with the signals at C(5)ÀC(8) and C(11).…”
mentioning
confidence: 78%
“…The absolute configuration of a number of nortriterpenods was unambiguously assigned by single-crystal X-ray diffraction using Cu or Mo Kα radiation. These include schilancitrilactone A, B, and C, 8 wuweizidilactone P, 9 arisanlactone A, 7 propindilactone H, 10 micrandilactone I, 6 micrandilactone H, 5 lancolides A, B, C, and D, 11 preschisanartanin O, 11 lancifonin A, 12 schicagenin A, 13 rubrifloradilactone C, 14 and wilsonianadilactone A 15 (Figure 1). However, a crystal that diffracts well to solve absolute configuration directly is always challenging.…”
Section: Methods To Assign the Absolute Stereochemistrymentioning
confidence: 99%